THE ATTITUDE OF THE CADET PARTY LEADER P. N. MILYUKOV TO THE ARMENIAN ISSUE - Velichko, Ludmila (Гуманитарные и юридические исследования, 2021)
The article reveals the attitude of the leader of the party of constitutional democrats P.N. Milyukov to one of the most relevant at the beginning of the XX century for Russia, foreign policy problems, namely an Armenian question. Since representatives of the Cadet Party were deputies of the State Duma of four convocations, and its representatives, above all Milyukov, who took over as Minister of Foreign Affairs of the Provisional Government in 1917, influenced the actions of the government and the emperor, an account of his views is key in understanding Russia’s foreign policy in the first third of XX century. The problem of the straits, which was on the foreign policy agenda since the emergence of the «Eastern Question», the manifestation of the internal political crisis in the Ottoman Empire, which entailed a discussion of its territorial integrity, became the context for the «Armenian question», which was also considered by Milyukov inseparably with domestic politics and the problem of national structure of the Russian state. The research is based on various types of historical sources: official statements, decrees and resolutions of state governing bodies; journalistic sources, data from periodicals and the memoirs of P.N. Milyukov. Their analysis allows us to see the idea of the cadets that foreign policy is the continuation of the internal one, which was expressed in the formation of the idea of a national structure of the state on the principles of national and cultural autonomy, and determined the cadets’ understanding of the place and role of Russia in the geopolitical space. The author made an attempt to show how the program requirements of the Cadet party, passing through a tough internal party discussion, were embodied in real political events thanks to the efforts of its leader, P.N. Milyukov. His position was controversial, which was expressed in determining the post-war status of Poland, Finland, as well as understanding the fate of Western Armenia. However, his public activities influenced the public perception of the problem and the adoption of foreign policy decisions.